Sosialisasi dan Implementasi Ejaan Bahasa Indonesia yang Disempurnakan untuk Perbaikan Penamaan bagi Villa di Wisata Kemuning, Karanganyar, Jawa Tengah - Kundharu Saddhono; Muhammad Rohmadi; Budhi Setiawan; Raheni Suhita; Ani Rakhmawati; Sri Hastuti (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The Enactment of Law No. 24 of 2009 concerning the Flag, Language, and State Emblem and National Anthem which is emphasized by Government Regulation No. 57 of 2014, Regulation of the Minister of Education and Culture No. 42 of 2018, and Decree No. 0424/I/BS.00.01/2022 must of course be obeyed by all Indonesian citizens. Public obedience to the law is still low, especially related to language. For example, many place names in public areas still use foreign languages. It is clear that the use of language violates the law, especially with regard to language. Enforcement of the law must be spearheaded by the government itself. If the community can obey the law, socialization to the general public will be smoother. Governance in government and private agencies is one of those regulated in the Law, especially Article 33 paragraph 1 which reads "Indonesian must be used in official communication in the government and private work environment". It is clear here that the standard variety of Indonesian must be used by private agencies in public information, especially lodging in tourist attractions such as in Kemuning Karanganyar. As a popular private institution, the enforcement of the implementation of the law mentioned above is the main pillar and an example for the wider community. Therefore, naming in private institutions must be managed properly. As a result of several observations, many villa naming in the Kemuning Karanganyar tourist area focuses more on non-linguistic factors, such as the form of naming, type of service, official stamps, envelopes used and archive storage. Linguistic problems, such as spelling errors, word selection errors, sentence meaning errors, sentence composition errors, are rarely noticed. There are many naming versions sent by the inn, especially in villas in Kemuning tourism. There are many variations and there is no standard related to this planter because the manager does not have a standard guideline. There are so many mistakes made by Villa managers in making naming. The target group of the HGR PKM program is Villas in a tourist area in Kemuning, Karanganyar, Central Java Province.